Hubungan Antara Kadar Asam Urat dengan Kepatuhan Minum Obat pada Pasien Tuberculosis Paru - Qurrotu A'yuni Auliya; Mochamad Rizal Maulana; Djoko Priyatno (Jaringan Laboratorium Medis, 2023)
Tuberculosis lungs is disease infectious disease caused by bacteria Mycobacterium tuberculosis. TB disease still become threat health Indonesian society which leads to illness , disability and death tall so that need exists countermeasures. Research objectives know connection between rate sour tendon with obedience drink medication in pulmonary TB patients. Study This is study retrospective analytic observational with approach cross sectional, with use analysis Research Chi square test statistics conducted at the Ambarawa Community Health Center (BALKESMAS) in October 2022. Population all moderate pulmonary TB patients undergo treatment at BALKESMAS Ambarawa. Research sample This of the total population namely 30 patients. Results from 30 respondents there is rate sour veins in patients Tuberculosis lungs there is enhancement rate sour tendon namely 11 respondents that is man with average levels sour urate 7.08 mg/dL (6 respondents ), female with average level 6.41 mg/dL (5 respondents ). Based on forever drink drug obtained that amount patient with treatment 3 months 57%, 2-3 months 30%, and 1 month 13%. Based on characteristics that kind sex men 53% and kind sex women 47%. Based on characteristics age category teenagers 23%, adults 50% elderly 27%. Based on obedience drink anti-tuberculosis drugs by 28 respondents or 93.34% of total number of respondents . Whereas For respondents who did not obedient drink drug namely 2 respondents or 6.06%. Chi square test results on compliance status drink medicine, type gender, age No showing connection significant (P0.05) against rate sour veins in patients Tuberculosis lungs. Research conclusions This No There is connection rate sour tendon with obedience drink medication in pulmonary TB patients, This caused by TB Treatment consists of over 2 stages that is intensive and advanced, function system immunity body relate with age, history of medication, obesity, consumption purines , and alcohol.